Communicating Desperation: Palestinians’ Suicide Bombing in Hallaj’s Novel Refugee without Refuge - Wuraafi, Ebrahim Mohammed (Journal of History Culture and Art Research, 2020)
The Palestinian-Israeli conflict is one of the thorniest conflicts in the world. The life of the Palestinians in refugee camps under occupation is very difficult. Curfews, checkpoints, detention, and violence permeate all aspects of their daily life. Striving against poverty, their vicious enemy, and the constant struggle to survive are daily nightmares. However, they are often perceived as terrorists and war criminals. Dixiane Hallaj’s Refugee without Refuge: A Novel of One Palestinian Family is an attempt to highlight the problems Palestinians face in the refugee camps in occupied Palestine. The novel engages in establishing the relationship between the horrendous living conditions of the Palestinians and the aggression of the Israeli occupation forces on one hand and the violent reaction of the Palestinians on the other. It demonstrates that suicide bombing committed by the Palestinians is a rebounding of the Israeli violence and atrocities exercised against the Palestinians and that such lethal acts have no relation to religion or politics. They are personal decisions and acts taken after a long tragic suffering under the yoke of occupation. This article argues that Hallaj’s novel challenges the familiar notions and preconceptions of Palestinians as violence agitators, suicide bombers, and terrorists, which are propagated by western media and literature. The article focuses on Hallaj’s depiction of the Palestinian suffering and their final determination to get rid of their persecutors using violence after all nonviolent means become impossible. Psychoanalysis theory is applied to the novel to criticize the protagonist’s motives to attempt suicide bombing.